Improving Cadres Knowledge and Skills in Non-Communicable Disease Control and Care in Kulonprogo, Yogyakarta - Arini, Merita; Prakoso, Denny Anggoro; Suratini; Primastuti, Harumi Iring (Universitas Airlangga, 2025)
Non-communicable disease (NCD) necessitates prolonged continuous intervention that impacts enormous morbidity, mortality, and socioeconomic repercussions on a global scale. Community and private primary healthcare facilities need to be more interconnected, although they have significant roles in NCDs' prevention and care. Aims: To enhance the community's competencies regarding NCDs through the involvement of private primary care. Method: The method used was a quasi-experiment (non-control, nonrandomisation) with the 'Aisyiyah Clinic involvement as the mentor for participants. The study involved 41 faith-affiliated cadres from 'Aisyiyah and Nasyiatul Aisyiyah, Kulonprogo, Yogyakarta Special Region Province, Indonesia. Interventions include health education sessions on NCDs and essential health examinations for NCD screening practices. The study evaluation was conducted using a pre-test and post-test of knowledge and skill observation checklist, followed by the Wilcoxon signed-rank, Spearman, and Kruskal-Wallis tests. Results: Education and practices increased participants' knowledge of NCDs (p=0.000) with a large effect size (r=0.50). The cadres also observed that they could perform their competencies in these examinations (100%). Additionally, there was no significant difference in knowledge (pre-test and post-test) based on cadres’ demographic background (p>0.05). In contrast, there was a significant difference in initial knowledge (pre-test), according to both duration of time as a cadre (p = 0.011). Conclusion: Health education and practices effectively increase health cadres' knowledge and skills related to NCD control. Simultaneously with continuous community empowerment, the study findings highlight a need for better integration between public health initiatives and private sector resources to sustainably improve the community health workers' role.